Visual media in motion: Conceptualizing the short video format within visual platforms - Guerra, Giulia Isabella (AoIR Selected Papers of Internet Research, 2026)
Social media have become increasingly visually focused with the rise of visual-centricplatforms like Instagram and TikTok, reshaping aesthetics and user experience. Inthese mobile-first spaces, vertical short videos redefined digital storytelling, contentcreation, and engagement. Although their relevance has fostered a rich and expandingbody of research, a conceptualization of “short videos” remains elusive, with varyingterminology across studies. Moreover, research on visual communication hasextensively focused on static images, while missing conceptual work with respect tomoving images designed for mobile consumption. Developing a conceptual frameworkis therefore essential, providing the foundation for systematically analyzing theseaudiovisual artifacts.Drawing from format theory, social media studies, multimodality and visualcommunication, this work introduces a conceptualization of short videos as a distinctivemedia format, defined by structural characteristics that allow to distinguish and analyzethem across platforms. This work outlines the technical infrastructure and audiovisualfeatures of the format, discussing how the interplay of diverse modes of communicationfosters both collective and individual experiences, thereby shaping meaning making.This conceptual framework expands research on moving images in mobileenvironments, offering a comprehensive understanding of the role of short videos within visual and social media culture and supporting methodologies to examine theirmultimodal components.